The Urban Review Issues and Ideas in Education - Hughes, Sherick A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Urban Review provides a forum for the presentation of original investigations, reviews, and essays which examine the issues basic to the improvement of urban schooling and education. The broad scope of topics presented reflects awareness of the multidisciplinary nature of contemporary educational problems.
Keywords: Education; Sociology; Community psychology; Environmental psychology; Education, general; Community and Environmental Psychology; Sociology, general